Photovoltaics for Community Service Facilities : Guidance for Sustainability - Africa Renewable Energy Access Program (World Bank, Washington, DC, 2017)
In many developing countries with large rural populations and low rural electrification rates, most community health and education facilities lack access to electricity. For facilities in remote areas beyond reach of the national grid, photovoltaic's (PV) systems may offer the most practical and least-cost way to access electricity. A PV system uses predictable solar resources and has long been cost competitive with diesel generators and other alternatives. In off-grid rural primary schools and health dispensaries, for example, PV systems oftentimes are an appropriate way to run many low-power, high-value appliances and equipment, from lamps and vaccine refrigerators to water pumps, television sets, and computers. Thus, if the electricity grid is not expected to arrive in the near future or if diesel fuel is unavailable or too expensive, a PV system may offer the least-cost technology for providing electricity service. If this rapid assessment determines that PV is a viable option, it results in a brief concept for a possible project and the plan for its preparation. The project concept is discussed with stakeholders and independent specialists, including off-grid renewable energy specialists, and is adjusted as appropriate. The plan for project preparation takes into account an assessment of available information and activities to be undertaken during preparation to fill gaps and generate additional and improved data. The second phase of project development is the preparation of the PV implementation plan. This is accomplished with the assistance of several specialists, including a PV technical specialist, and involves working closely with lead organization managers and specialists, broad-based stakeholder consultations, and multiple iterations. The third phase of project development, procurements and contract management, involves securing firm financing commitments (including those for post-project recurrent costs), developing tender packages, tendering and contracting, and contract management. The fourth phase, long-term operation, is where too many projects fail. In summary, this toolkit is, at a minimum, a checklist of key issues to address in developing an institutional PV project. While it is not a technical manual, nor a substitute for using professional PV specialists to size, configure, and specify system and maintenance requirements, it offers practical operational guidance to assess, develop, and implement projects with PV systems in ways that enhance cost effective supply and sustainable post-project operations. The guidance offered herein demonstrates that the opportunities for effectively addressing the issues to establish the basis for sustainability are many.